The Developing of English Debate E-Flipook for English Club - Ririn Mirnawati; Winda Trisnawati; Levandra Balti (UM Purwokerto Press, 2024)
This research was conducted to overcome the obstacles encountered by students in debating in English Education Department of Universitas Muhammadiyah Muara Bungo. Based on the pre-observation, do the interview of some students and teachers that this English club need guidance book for students to practicing in English debate, based on pre-observation result the students interest to conduct this research to develop debate guidance book. Based on the problem analysis, it was found that many students have lack of vocabulary and pronunciation errors. Besides that, they still have lack of students' level of criticality in mastering the material when debating. This research used Research and Development methods (R&D) with 4D model. The data collection techniques used include interview and questionnaire. The research subjects were students of the English Club at Muara Bungo University. The instrument used in this research is the E-Flipbook design process, after that Expert Validation consisting of material experts and media experts, and the last is the Practicality questionnaire.The results of this study are 1). the score obtained for material validation was 84% with a valid category, and media validation was 89% with a very valid category, 2). the student's practicality score was 87% with a very valid category, and the lecturer's practicality score was 87% with a very valid category. then this study shows that the E-Flipbook English debate guidebook is very valid to be used especially for English club students.